2016
DOI: 10.1103/physreve.94.012147
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Hermitian ensemble of random Gaussian matrices

Abstract: It is shown how pseudo-Hermiticity, a necessary condition satisfied by operators of PT symmetric systems can be introduced in the three Gaussian classes of random matrix theory. The model describes transitions from real eigenvalues to a situation in which, apart from a residual number, the eigenvalues are complex conjugate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…As expected, the ellipse is widened for increasing disorder. This elliptical pattern, instead of a circular one, is a consequence of the existence of the real nearest-neighbor couplings 82,83 . We can also observe that, in general, the modes around the center of the elliptical pattern are the most extended (c) W=5 Figure 1.…”
Section: Non-hermitian Disorder In Coupled Systemsmentioning
confidence: 93%
“…As expected, the ellipse is widened for increasing disorder. This elliptical pattern, instead of a circular one, is a consequence of the existence of the real nearest-neighbor couplings 82,83 . We can also observe that, in general, the modes around the center of the elliptical pattern are the most extended (c) W=5 Figure 1.…”
Section: Non-hermitian Disorder In Coupled Systemsmentioning
confidence: 93%
“…which can distort a symmetric matrix into pseudosymmetric matrix P (k) = (R + R t )K, note that KP K −1 = P t , namely, P (k) are pseudo-symmetric under K. This metric has also been utilized earlier [18]. Another class of pseudo-symmetric matrices is Q(k) which is distortion a symmetric matrix by a factor k as…”
Section: Various Real Pseudo-symmetric Matricesmentioning
confidence: 99%
“…The fact that real symmetric and Hermitian random matrices make two separate classes of ensembles GOE and GUE having distinct statistical properties, motivates us to separate pesudo-symmetric real matrices from the more general pseudo-Hermitian matrices [16][17][18][19]. In the present work, we invoke a lesser class of matrices which are real pseudo-symmetric under a metric η such that ηHη −1 = H t , these are essentially non-symmetric ones.…”
Section: Introductionmentioning
confidence: 99%
“…12, it is shown that for the pHGOE class, the result can be fitted with both Eqs. (11) and (10), yielding a value compatible with µ = 2 which implies in a cubic repulsion. In Fig.…”
Section: B Complex Eigenvalues Statisticsmentioning
confidence: 96%
“…From the matrices of these ensembles, an ensemble of pseudo-Hermtian Gaussian matrices can be constructed as [10,11] A = P HP + QHQ + r(P HQ − QHP ),…”
Section: Overview Of the Pseudo-hermitian Gaussian Ensemble Stud-iedmentioning
confidence: 99%